Policy Strategies for Road Infrastructure Planning and Budgeting in West Sumatra - Irza, Hamdi (Jurnal Administrasi dan Kebijakan Publik, 2025)
Infrastructure planning and budgeting policies in West Sumatra Province have not been effective in reducing spatial inequality, as basic services such as transportation, drinking water, and sanitation remain unevenly distributed. The transportation sector, despite having the highest forward linkage value (1.67) and serving as a key driver for other sectors, demonstrates suboptimal performance, reflected in an Incremental Output Ratio (ICOR) of 6.8%, well above the ideal benchmark of 3–4%. Limited regional fiscal capacity, compounded by mandatory spending obligations in education, health, and other sectors, further restricts the allocation of resources for road development and management. Within this context, the available policy choices are to increase revenue, spend more effectively, or adopt creative financing schemes. This study aims to formulate policy recommendations for road infrastructure planning and budgeting that contribute to reducing regional disparities, employing the Analytical Hierarchy Process (AHP) method based on the preferences of key policymakers in the West Sumatra Provincial Government. The analysis indicates that a better spending strategy is the most preferred option. Its successful implementation, however, requires strong political commitment from regional leaders and legislators, a cultural and organizational shift among stakeholders in infrastructure governance, and the reinforcement of legal mechanisms through more effective systems of program monitoring and evaluation.